Prestasi Belajar Akuntansi Perusahaan Jasa Ditinjau Dari Perhatian Mahasiswa Dalam Pembelajaran Dan Kreativitas Belajar Pada Mahasiswa Program Studi Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah SurakartaAngkatan 2015 - Aminah, Siti; , Dr.Suyatmini,SE.,M.Si; , Drs. Sudarto H.S., MM (2016)
Learning Achievement Company Accounting Services Seen From Attention Students in Learning and Creativity Learning On Student Accounting Studies Program Faculty of Teacher Training and Educational Sciences University of Muhammadiyah Surakarta, 2015. Forces Study Program of Accounting Education the Faculty of Education, University of Muhammadiyah Surakarta, 2016. The purpose of this study was to determine: 1) the influence of the attention of students in learning on student achievement, 2) the influence of creativity of student learning on student achievement, 3) the influence of the attention of students in learning and creativity of student learning on student achievement. Associative Quantitative methods used. Inroads in this research were 251 students with a sample of 146 students were taken by proportional random sampling technique in a random way. The data collection technique using a questionnaire that has been tested with the validity and reliability. Data analysis technique used is multiple linear regression analysis. Results of regression analysis regression equation: Y = 26.197 + 0.387 (X1) + 0,579 (X2), which means the achievement of student learning is influenced by the attention of students in learning and creativity of student learning. Based on the analysis and discussion can be concluded that: (1) the attention of students in the learning of a significant effect on student achievement. It is evident from the regression analysis obtained a value> is 3, 583> 1,977 with significant value 0.000 <0.05. (2) creativity of student learning significantly to the achievement of students. It is evident from the regression analysis obtained a value> ie 4.661> 1.977 with 0.000 significance value <0.05. (3) Attention students in learning and creativity of students learning together have a significant effect on student achievement. It is evident from the regression analysis obtained a value> ie 31.308> 3.059 with 0.000 significance value <0.05. (4) Variable Attention students in learning contribute effectively amounted to 12.5%. Variable creativity of student learning contribute effectively by 18%, bringing the total effective contribution both by 30.5%, while 69.5% are influenced by other variables not examined. keywords: Learning , Creativity , Student , Learning , Attention , Achievement